A Román királyság Nyugati erődrendszere : történeti-földrajzi vázlat - Suba, János (Közép-Európai Közlemények, 2012)
In order to enhance the defence of Romania, a line of forts was constructed with the help of French advisors, and British and French funding. Construction of the lines started in 1937 and it fortified the Western border of the country (the one with Hungary). The present paper examines the role of the forts in the state’s concept of defence and the connection between the structuring, development and dislocation of the armed forces and the fortifications. The role of the lines was to provide cover for the eventual mobilisation of the Romanian army in the valley of the River Szamos from North and in the valley of the River Maros from South. Running parallel with the border, the lines extended 300 km long from the River Tisza to the River Maros. It was named after King Charles II of Romania. The establishment of the Romanian lines was based on the actual assessment of the state’s situation and there were well-founded strategic reasons behind it. Even though the lines never became the venue for armed conflicts, its mere existence had a dissuasive power in the service of Romania’s interests.